2020
DOI: 10.1080/16878507.2020.1719336
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of essential oils incorporated chitosan-based cues with antibacterial and antifungal potentialities

Abstract: Herein, we report the characterization of chitosan-based cues incorporated with two different essential oils, i.e., tea tree oil (TTO) and clove oil (CO). The essential oils incorporated chitosanbased cues offer considerable solutions to eliminate pathogenic infections and/or to reduce microbial contaminations in healthcare facilities. In this background, chitosan(CST)-based cues were incorporated with TTO and CO and final cues were designated as CST-TTO and CST-CO. The loading efficiency was optimal in CST-TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…As far as EOs are concerned, an extensive review of the literature shows that, over time, they have been increasingly attracting the interest of researchers. Clove [ 102 , 103 , 104 , 105 , 106 ] and thyme [ 107 , 108 , 109 , 110 , 111 ] EOs have been largely used in encapsulation studies, mostly through the ionic gelation technique, targetingdifferent applications. However, a wide range of EOs-based chitosan nanoparticles have also been referred to the literature over the last five years, such as mint ( Mentha piperita ) [ 111 , 112 ], cardamom [ 113 ], krill oil ( Euphausia superba ) [ 114 ], lime [ 115 ], orange [ 116 ], lavender [ 109 , 116 ], Achillea millefolium [ 117 ], Cymbopogon martini [ 118 ], citrus [ 119 ], Piper nigrum [ 120 ], peppermint or green tea EOs [ 3 , 121 ].…”
Section: Chitosan As a Matrix For Nanosystemspreparation: Methodsmentioning
confidence: 99%
“…As far as EOs are concerned, an extensive review of the literature shows that, over time, they have been increasingly attracting the interest of researchers. Clove [ 102 , 103 , 104 , 105 , 106 ] and thyme [ 107 , 108 , 109 , 110 , 111 ] EOs have been largely used in encapsulation studies, mostly through the ionic gelation technique, targetingdifferent applications. However, a wide range of EOs-based chitosan nanoparticles have also been referred to the literature over the last five years, such as mint ( Mentha piperita ) [ 111 , 112 ], cardamom [ 113 ], krill oil ( Euphausia superba ) [ 114 ], lime [ 115 ], orange [ 116 ], lavender [ 109 , 116 ], Achillea millefolium [ 117 ], Cymbopogon martini [ 118 ], citrus [ 119 ], Piper nigrum [ 120 ], peppermint or green tea EOs [ 3 , 121 ].…”
Section: Chitosan As a Matrix For Nanosystemspreparation: Methodsmentioning
confidence: 99%
“…The dried bark of this tree is conventionally used in Pakistan for improving oral hygiene and promoting teeth brightening. Earlier studies reported the antimicrobial activity of this plant against bacteria and fungi that may be due to the presence of polyphenols 1,2,[9][10][11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…The emergence and spread of multidrugresistant (MDR) pathogens are one of the most serious threats to successful treatment of microbial diseases 1 . According to the World Health Organization (WHO), infectious diseases are the 3rd most significant cause of mortality worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A temperature-sensitive packaging material has been developed to give an indication of the quality status of fresh beef during storage [ 248 ]. Fish and other seafood products are also highly perishable foods as a result of microbial spoilage and oxidative reactions [ 249 , 250 ]. Active and smart packaging materials have also been shown to be effective at protecting these products, as well as at monitoring their quality during storage [ 28 , 79 , 112 , 236 ].…”
Section: Applications Of Biodegradable Packaging Materialsmentioning
confidence: 99%